2017
DOI: 10.1016/j.je.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Living status and frequency of eating out-of-home foods in relation to nutritional adequacy in 4,017 Japanese female dietetic students aged 18–20 years: A multicenter cross-sectional study

Abstract: BackgroundLiving status (e.g., living with family or alone) may affect dietary habits. We compared nutritional adequacy according to living status and the frequency of eating out-of-home foods in young Japanese women.MethodsFemale dietetic students (aged 18–20 years; n = 4,017) participated in a cross-sectional multicenter study, which was conducted in 85 dietetic schools in 35 of 47 prefectures in Japan. Habitual dietary intake was assessed with a validated diet history questionnaire. Nutritional adequacy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 35 publications
8
36
0
2
Order By: Relevance
“…There was little to no nutrient inadequacy of protein, vitamin B 12 and Cu among the entire study population (incidence: 0 %). The proportion of Japanese adolescent girls (46) and young women (36) with insufficient intakes of these nutrients was reported to be very small, and thus these reports are consistent with our present findings. In other words, protein, vitamin B 12 and Cu might be nutrients which are sufficiently consumed by Japanese people, and the adequacy of these nutrients may not be related to breakfast skipping.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was little to no nutrient inadequacy of protein, vitamin B 12 and Cu among the entire study population (incidence: 0 %). The proportion of Japanese adolescent girls (46) and young women (36) with insufficient intakes of these nutrients was reported to be very small, and thus these reports are consistent with our present findings. In other words, protein, vitamin B 12 and Cu might be nutrients which are sufficiently consumed by Japanese people, and the adequacy of these nutrients may not be related to breakfast skipping.…”
Section: Discussionsupporting
confidence: 92%
“…Inadequacy of intake for each nutrient was determined by comparing nutrient levels with each dietary reference value according to the Japanese DRI using a previously reported method (35)(36)(37) . Different types of dietary reference values comprising the Japanese DRI were established according to their purpose.…”
Section: Determination Of Habitual Nutrient Intake Inadequacymentioning
confidence: 99%
“…These results were consistent with those from previous studies that showed a higher frequency of eating out among men and younger adults when compared with that among older adults [13,41], or higher proportion of eating out in men than women [13]. Similar to a previous study among Japanese university students [36], living alone was associated with a higher frequency of eating meals prepared away from home. In addition, women living in urban areas had less home-cooked meal consumption, which is consistent with the result of a Vietnamese study.…”
Section: Discussionsupporting
confidence: 92%
“…Logistic regression analysis was used to examine the difference in the prevalence of meeting DRIs based on the Low and Middle groups according to the frequency of the home-cooked meal consumption compared with the High group in the crude and adjusted model. Confounding factors considered in the adjusted model were age category (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and 51-64 years), occupation (professional/manager, sales/service/clerical, security/transportation/labour, student, housekeeper, and not in paid employment), living alone or not (yes or no), region (Hokkaido/Tohoku, Kanto, Hokuriku/Tokai, Kinki, Shikoku/Chugoku, Kyusyu), current smoker (yes or no) and habitual alcohol drinker (yes or no), which was reported as a factor affecting the frequency of consumption of meals prepared away from home [8,27]. All statistical analyses were performed with SAS statistical software, version 9.4 (SAS Institute Inc., Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation